Solar Variability Induced in a Dynamo Code by Realistic Meridional Circulation Variations - Lopes, I; Passos, D (My University, 2009)
In this work we use an already-published method to infer a variation profile for the solar meridional circulation over the last 250 years. We feed this variation profile into a numerical dynamo code, and we reconstruct a sunspot time series that acts as a proxy for solar cycle activity. We perform three simulations with slightly different parameters, and the results are compared with the observational data. The medium and large correlation coefficients between reconstructed and observational time series seem to indicate that variations in meridional circulation play an important role in the modulation of solar activity.
Keywords: Sun; Solar Magnetic Cycle